Factors causing Dengue Hemorrhagic Fever (DHF) in Sikka District, East Nusa Tenggara Province - Kleden, Maria Agustina; Atti, Astri; Talahatu, Anna Henny (Jambura Journal of Biomathematics (JJBM), 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by infection of the Dengue virus. The incidence of Dengue Fever in Sikka District is the highest in East Nusa Tenggara Province and even in Indonesia at the beginning of 2020. The condition of DHF occurrence in Sikka District is designated as an Extraordinary Event (EE). This study aims to identify some factors including the home environment, biological environment, and social environment that might lead to the occurrence of DHF in Sikka Regency and to determine the risk of a person getting DHF based on the factors. There were 170 respondents from the community of Sikka Regency, where 85 of them have suffered from DHF while the other 85 have never had DHF. The instrument used was a questionnaire containing 22 questions that have been tested for validity and reliability. This is a quantitative study, where the analytical method used is the logistic regression analysis. The results of the analysis showed that the factors that affect a person suffering from DHF are the size of the house, the color of the walls of the house, the habit of draining water reservoirs, the habit of using mosquito repellent, and the participation in cleaning mosquito nests. Based on the value of the odds ratio, it is known that a person with a house area of 36 m2 is more at risk of contracting dengue fever than someone with a house area of 36 m2. Likewise, households that did not participate in cleaning mosquito nests were compared to those who did participate. It is also found that house members who have light wall colors, have a habit of draining water reservoirs, and have a habit of using mosquito repellent are more at risk of contracting DHF than family members whose walls are dark in color, do not have the habit of draining water reservoirs, and do not participate in cleaning mosquito nests.